Potent antagonistic activity of Egyptian Lactobacillus plantarum against multiresistant and virulent food-associated pathogens - Al-Madboly, Lamiaa A.; Abdullah, Abeer K. (Frontiers in Microbiology, 2015)
Recent years have showed a growing interest to replace the administration of antibiotics with the application of probiotics. The aim of our investigation was to screen for promising strains with broad antimicrobial activity and also more resistant to the challenges met in the gastrointestinal tract. In our study, only 32 out of the 50 (64%) probiotic isolates showed antagonistic activity against certain major extensively and pandrug-resistant Gram-positive and -negative food-borne pathogens. Fifteen L. plantarum isolates had a broad antibacterial spectrum. Among these isolates, only five presented potent antibacterial activity relative to previous studies. The recorded inhibition zone diameter ranged from 25 to 44 mm. Pronounced cell-free supernatant activities (6400-25600 AU/ml) were commonly detected at the end of the logarithmic phase at 37°C. A marked increase in the range of activity (12800-51200 AU/ml) was recorded after the addition of 0.9% NaCl to the media. Moreover, subjecting these isolates to different stressors, including high temperature, low pH, and different concentrations of bile and NaCl, revealed different responses, and only two out of the five L. plantarum isolates showed marked resistance to all of the stress factors. This study highlights the intense and broad antagonistic activity induced by L. plantarum against various food associated pathogens, and their ability to resist different stressors suggests that they can be used in the food and pharmaceutical industry.